PEMBERDAYAAN KELOMPOK TANI UNTUK MITIGASI PERTANIAN SKALA MIKRO DI MUSIM KEMARAU BERBASIS PUPUK BOKASHI DI DESA PASIRNANJUNG KABUPATEN SUMEDANG - Turmuktini, Tien; Ria, Roosma; Sri, Sri; Galang, Galang; Admijaya, D Tisna; Setiawibawa, L (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2020)
Farming in the dry season is a difficult job to do, because it is constrained by the limited availability of water. This situation occurred in the village of Pasirnanjung which caused agricultural activities to cease. In order that agriculture can continue to run, a micro-scale agricultural mitigation can be applied during dry-season by planting in polybags based on bokhasi fertilizer in the yard of the house. Bokashi is an organic material that can improve the physical, chemical and biological properties of the soil, that has an effect on plants growth and yield. Empowerment of farmers have been carried out in Pasirnanjung village, from August to September 2018, by the methode of counseling, training, demonstration and planting. The participants were joined by 14 groups, 11 farmer groups, 1 Putra Karya Sejahtera Youth Group, 1 Mawar Lestari Women’s Farmers Group and 1 Nanjung Jaya Gapoktan Group. Training materials include preparation of tools and materials, seedling of vegetable seeds, making bokashi, preparation of planting media, planting, cultivating and harvesting. As a result, each group can make bokashi and can grow vegetables in a polybag in their yard during the dry season. This activity will have a good impact on the acceleration of the realization the village government program to make agricultural education village and ecovillage.